Design and development of an IAGA compliant magnetic observatory - Othman, Mohd Khair (2007)
The first attempt to construct a magnetic observatory station was initiated in 2002 at Kolej Universiti Teknologi Tun Hussein Onn, presently known as Universiti Tun Hussein Onn Malaysia (Lat. 1.51° N , Long. 103.55° E), as a scientific facility equipped to detect and record daily scientific phenomena of the earth's magnetic field variations. Preliminary activities such as magnetic surveys, construction of non-magnetic station and coding a new data logger software were carried out. The proton overhauser and fluxgate magnetometers were used to measure the daily magnetic field variations. Daily field variables of the horizontal (H), declination (D) and vertical (Z) components were recorded every second and the total intensity (F) component was observed every 5 seconds daily. One-minute digital gaussian filter was applied to the data to minimise the effect of aliasing to produce the values of dH, dD and dZ. Between the months of June to December 2005, three geomagnetic phenomena were observed namely the magnetic field variations, magnetic storms and pulsations. Daily average variations of the dH (-0.5039 nT) component shows that it is low at night and maximises around local noon. The average dZ (0.2817 nT) shows an opposite variation to the dH, minimising at local noon. This is due to the east-west ionospheric current enhancement by solar radiation which is a maximum at local noon. The average dD (0.3741 nT) follows a similar variation to dH. However, the dD does not always follow the trend, due to very strong north-south components of the equatorial electroject (EEJ) current. The day-to-day variation of dD is influenced by the dawn to dusk effect and the EEJ current. Nine geomagnetic storms were detected during this period, with the most intense observed on 24 August 2005 with Dst = -216 and Kp = 9-. Eighty-five Pi 2 (f= 2 to 30 mHz) pulsations were also observed during magnetically quiet periods (Kp < 2+). The successful detection of these phenomena shows that quality magnetic data which comply with international measurement standards based on IAGA specifications can be observed.